2008
DOI: 10.1021/bi800445f
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Stable (αβ)4-Tetraprotomer from Na+/K+-ATPase Solubilized in the Presence of Short-Chain Fatty Acids

Abstract: Previously, it was demonstrated that acetate anions increase the higher oligomer (H), consuming (alphabeta) 2-diprotomer (D) and alphabeta-protomer (P) of solubilized dog kidney Na (+)/K (+)-ATPase [ Kobayashi, T. et al. (2007) J. Biochem. 142, 157-173 ]. Presently, short-chain fatty acids, such as propionate (Prop) and butyrate, have been substituted effectively for acetate. The molecular weight of 6.01 x 10 (5) for H and quantitative Na (+)/K (+)-dependent interconversion among H, D, and P showed that H was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…Neither in co-immunoprecipitation nor in cross-linking studies, however, do we find evidence of direct contact between caveolin-1 and any specific subunits of the other two oligomers. Our findings, in conjunction with previous extensive evidence of the higher oligomeric states of Na + /K + -ATPase promoters 14,15,29,30,32,39 and caveolin-1, 23,38 clearly indicate that interaction of caveolin-1 with kidney caveolar Na + /K + -ATPase occurs within a large oligomeric complex of caveolin-1, the annexin-2 tetramer, and Na + /K + -ATPase (Figure 9A).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Neither in co-immunoprecipitation nor in cross-linking studies, however, do we find evidence of direct contact between caveolin-1 and any specific subunits of the other two oligomers. Our findings, in conjunction with previous extensive evidence of the higher oligomeric states of Na + /K + -ATPase promoters 14,15,29,30,32,39 and caveolin-1, 23,38 clearly indicate that interaction of caveolin-1 with kidney caveolar Na + /K + -ATPase occurs within a large oligomeric complex of caveolin-1, the annexin-2 tetramer, and Na + /K + -ATPase (Figure 9A).…”
Section: Discussionsupporting
confidence: 90%
“…There are major differences between the lipid compositions of the caveolae–raft microdomains and the remainder of the plasma membrane (Figure 1B and ref (26)), and previous studies have clearly indicated effects of lipid on the catalytic activities and quaternary structure of Na + /K + -ATPase. 2830 It is also known that quaternary structure has profound effects on the reaction mechanism of the enzyme. 3133 Hence, we suggest the need for more rigorous investigations, e.g., those using transient kinetics, on the potential differences between the turnover cycles of the caveolar and noncaveolar preparations, and the possible physiological implications of such differences.…”
Section: Discussionmentioning
confidence: 99%
“…Although the α and β subunits are non-covalently linked in a minimal αβ-protomer structural unit [59], solubilized enzyme solutions contain other oligomers, such as (αβ)2, (αβ)3 and (αβ)4 as shown by chemical crosslinking [60]. HPLC analysis of solubilized Na + /K + -ATPase reveals that K + induces the conversion of protomer into diprotomer and/or higher oligomers while Na + has the opposite effect [61,62]. Cation and hence, conformation-dependent alteration in the oligomer equilibrium may occur through changes in exposure of the transmembrane domain of the β subunit as mutational analysis has shown that this portion of the protein mediates β-β homooligomerization, as well as α/β assembly [63].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, indeed, it was established that sarcoplasmic reticulum Ca 2ϩ -ATPase, solubilized as a monomer by C 12 E 8 , retains all of the basic features required to function as a Ca 2ϩ -transporting unit, regardless of the tendency of this Ca 2ϩ pump to undergo reversible and irreversible self-association (20). For Na ϩ ,K ϩ -ATPase, this also appears to be the case (28 -30), although dimerization of the ␣,␤-protomer is a more pronounced feature of this ATPase than it is for Ca 2ϩ -ATPase (27,(31)(32)(33). Application of the same surfactant strategy to H ϩ ,K ϩ -ATPase is fraught with the problem that it is difficult to avoid either irreversible or reversible inhibition of enzyme activity in the detergent-solubilized state.…”
Section: Surfactant Solubilization Of Tubular Vesicular Membranes Andmentioning
confidence: 97%
“…Despite the probable presence of protein-protein interactions in the native membrane, which may affect enzyme activity (25,26), they all indicate monomeric Ca 2ϩ -ATPase as the fundamental Ca 2ϩ -transporting unit. For Na ϩ ,K ϩ -ATPase, the evidence is more equivocal in that both monomeric and dimeric forms with retention of enzyme activity have been detected by analytical ultracentrifugation (27)(28)(29)(30) and by HPLC (31)(32)(33). The requirement of an oligomeric structure as a sine qua non to preserve transport and enzyme activity, as claimed for H ϩ ,K ϩ -ATPase and reported in a recent review (34), is not indicated by either the detergent data or by the available threedimensional x-ray diffraction structures of Ca 2ϩ -ATPase (35,36), Na ϩ ,K ϩ -ATPase (37)(38)(39), and H ϩ -ATPase (40,41).…”
mentioning
confidence: 99%